EXPLORING SUSTAINABLE MOBILITY IN HIGHER EDUCATION THROUGH STUDENT MOTORCYCLE PARKING BEHAVIOUR - Utomo, Heru Prasetiyo; Armanto, Fandi (Border: Jurnal Arsitektur, 2021)
In the face of global warming, all parts of the country are expected to take part in reducing the carbon footprint. This means that universities as the epicenter of education are also expected to optimize their role because universities have a big role in the mobilization of thousands of students every day. However, to bring sustainable mobility, the campus must be able to overcome many challenges, both in terms of infrastructure and campus management system. This study will examine the sustainable mobility that exists on the East Java “Veteran” National Development University (UPNVJT) campus through a study of the building structure which is reflected in the parking behavior of students' motorbikes. The study will be carried out through the method of observing existing conditions and assessing the condition of UPNVJT campus infrastructure on sustainable mobility. Data from respondents is also used to explain student parking behavior in response to campus infrastructure arrangements. The results of this study indicate that the arrangement of the UPNVJT building still does not reflect optimal sustainable mobility. This is indicated by the behavior of mobilization which still relies a lot on the use of motorized vehicles even for mobilizing activities with a fairly short distance.